Does evidence of network effects on firm performance in pooled cross‐section support prescriptions for network strategy? - Baum, Joel A. C.; Cowan, Robin; Jonard, Nicolas (Strategic Management Journal, 2014)
Strategic prescriptions drawn from pooled cross‐sectional evidence of firm performance effects are not necessarily warranted. This is because firm characteristics can influence both the mean and variance of firm performance. Strategic inferences are warranted if empirically observed effects reflect increases in mean firm performance. If they reflect increases in firm performance variance, however, such inferences are warranted only if the increased odds of achieving high performance compensate sufficiently for the concomitantly increased risk of realizing poor performance. Our simulation study, which contrasts firm performance effects in pooled cross‐section and within‐firm over time, counsels caution when basing strategic prescriptions on pooled cross‐sectional studies of firm performance in general, and in the case of network effects in particular . Copyright © 2013 John Wiley & Sons, Ltd.